Armchair explorer - Isalska, Anita (Lonely Planet guidebooks., 2021)
Calling culture lovers: sample music, films and books from 120 countries without leaving your armchair. Perfect preparation for travellers or simply a satisfying journey into the unknown, this book lists the five most interesting books and movies from each country, plus its top ten tunes. Be introduced to Ethiopian jazz, French new wave cinema, Irish poetry and more. Discover a little of each countries' life and soul through each recommendation by Lonely Planet's experts as well as dedicated sections that dive deep into special topics that range from South Korean K-Pop to Belgian graphic novels.